Cyber Warfare Building the Scientific Foundation - Jajodia, Sushil; Shakarian, Paulo; Subrahmanian, V.S.; Swarup, Vipin; Wang, Cliff; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book features a wide spectrum of the latest computer science research relating to cyber warfare, including military and policy dimensions. It is the first book to explore the scientific foundation of cyber warfare and features research from the areas of artificial intelligence, game theory, programming languages, graph theory and more. The high-level approach and emphasis on scientific rigor provides insights on ways to improve cyber warfare defense worldwide. Cyber Warfare: Building the Scientific Foundation targets researchers and practitioners working in cyber security, especially government employees or contractors. Advanced-level students in computer science and electrical engineering with an interest in security will also find this content valuable as a secondary textbook or reference.
Cyber War Games -- Alternatives to Cyber Warfare: Deterrence and Assurance -- Identifying and Exploiting the Cyber High Ground with Botnets -- Attribution, Temptation, and Expectation: A Formal Framework for Defense-by-Deception in Cyberfare -- Game-theoretic Foundations for the Strategic Use of Honeypots in Network Security -- Cyber Counterdeception: How to Detect Denial & Deception -- Automated Adversary Profiling -- Cyber Attribution: An Argumentation-Based Approach -- The Human Factor in Cybersecurity: Robust & Intelligent Defense -- CyberWar Game: A Paradigm for Understanding New Challenges of Cyber War -- Active Discovery of Hidden Profiles in Social Networks using Malware -- A Survery of Community Detection Algorithms Based on Analysis-Intent -- Understanding the Vulnerability Lifecycle for Risk Assessment and Defense Against Sophisticated Cyber Attacks -- Graph Mining for Cyber Security -- Programming language theoretic security in the real world: a mirage or the future?.
Keywords: Computer security; Data encryption (Computer science).; Computer communication systems; Application software; Systems and Data Security; Cryptology; Computer Communication Networks; Information Systems Applications (incl. Internet).